Comparison of the economic benefits and the payback periods of rooftop solar panels in Australia - Hayat, M.; Shahnia, Farhad; Arefi, A.; Iu, H.; Fernando, T. (IEEE, 2018)
© 2017 IEEE. Installation of a solar system by a household is a big decision, and there are many factors which need to be considered before this decision. It can be highly rewarding in some cases and for others, it may bring a loss in the investment. The main factors which need to be considered are the electricity consumption tariff, electricity consumption pattern, the location of the household and the tariffs offered by the utility in that area. In this paper, economic incentives of installing a rooftop solar panel and battery system are discussed for a household in different states served by various utilities. A comparison is made to find which states are more suitable in terms of gaining financial benefits from rooftop solar panels.